GAMBARAN SPASIAL KADAR FLOUR JARINGAN PDAM BERBASIS GOOGLE EARTH - Hadnyanawati, Hestieyonini (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
One source of drinking water used by the public is the water coming from local water company. One is the water content in flour. The content of fluorine in drinking water must comply with the limit. Flour is an essential element because of its role in bone mineralization and hardening tooth enamel. Shortage of flour in the water can cause dental caries, and if the excess flour can cause spots on tooth enamel formation occurs at the time of the email (fluorosis). For it is necessary for the measurement of fluorine content of drinking water. Measurement of tissue levels of flour local water company in the study was conducted at nine locations including sources of water, well pump, and installation of network local water company in District Sumbersari Jember. Data from these measurements are presented in spatial and non spatial. To give an idea of spatial levels of network taps flour is used geographic information system-based Google Earth. The results of measurements of fluoride levels in drinking water local water company in the District Sumbersari Jember obtained the average 0.18 ppm.